Efficacy and Usefulness of New Single‐Needle Intensive Granulocyte and Monocyte Adsorptive Apheresis in Active Ulcerative Colitis Patients Without Corticosteroids and Biologics. Issue 4 (August 2016) - Shimazu, Keiji; Fukuchi, Takumi; Kim, Insung; Noguchi, Yuki; Iwata, Megumi; Koyama, Shintaro; Ubukata, Satoshi; Tanaka, Atsuo
Abstract: Intensive granulocyte and monocyte adsorptive apheresis (GMA) twice weekly is effective and safe for patients with active ulcerative colitis (UC), but the requirement for maintaining two blood access routes is problematic. Here we compared the efficacy and safety of one‐route blood access intensive GMA using a single‐needle (SN) and conventional two‐route blood access intensive GMA using a double‐needle (DN) in patients with active UC not undergoing corticosteroid therapy. Among 80 active UC patients, 38 patients received SN intensive GMA and 42 patients received DN intensive GMA. The clinical remission ratio and mucosal healing ratio at 6 weeks, and the cumulative non‐relapse ratio at 52 weeks did not differ significantly between groups. In addition, no serious or mild adverse effects were observed in SN intensive GMA. SN intensive GMA may be an adequate and novel therapeutic option for active UC as an alternative therapy before using corticosteroids.